Pine afforestation changes more strongly community structure than ecosystem functioning in grassland mountain streams - Principe, Romina Elizabeth (2015)
In the past decades, afforestation of grassland landscapes has gained importance both as an economic activity and a mechanism to mitigate anthropogenic carbon emissions. This study evaluates the effect of pine afforestation on grassland streams analyzing changes in two integrative ecological indicators: leaf litter breakdown and primary production. We compare those results with changes in structural attributes of benthic biota (primary producers and invertebrates). Six contiguous first-order streams were selected in the upper basin of the Ctalamochita river (Córdoba, Argentina): three reference streams draining grasslands and three streams draining Pinus elliottii afforestations. Two in situ experiments were performed to compare leaf litter breakdown and primary production between grassland and afforested streams. Additionally, invertebrate assemblages in leaf litter and riffles, and periphyton standing stock were sampled and assessed. Nine out of 26 structural indicators showed differences between stream types but indicators measuring changes at the basal level of the food web (i.e. detritus and primary producers) were less sensitive than those recording changes in consumers. Our attempt to measure direction and magnitude of changes on stream functioning following afforestation was halted by our simple implemented methodology (i.e. leaf pack method for leaf litter decay and biofilm accrual on natural stone substrates for primary production assessments); only 1 out of 4 indicators differed. We argue that the lack of strong differences in elemental measurements of primary production and needle decay between afforested and grassland streams resulted from compensating opposing forces controlling such processes, i.e. higher grazing vs. higher sunlight in grassland streams and higher shredding vs. lower microbial decomposition mediated by lower temperature in afforested streams. Attributes related to the invertebrate compartment showed the highest sensitivity to afforestation, emphasizing their value as biological indicators of stream ecological integrity.